Introgression from cultivated rice alters genetic structures of wild relative populations: implications for in situ conservation. Issue 1 (16th October 2017) - Jin, Xin; Chen, Yu; Liu, Ping; Li, Chen; Cai, Xingxing; Rong, Jun; Lu, Bao-Rong
Abstract : We found gene introgression from cultivated rice to its in situ conserved wild relative populations, which has considerably altered their genetic structure and relationship. The level of introgression is associated with the spatial distances of the wild populations from cultivated rice fields. The findings are based on genetic analyses of six wild populations and two sets of rice cultivars using two types of molecular markers. Crop-wild introgression alters the genetic integrity of wild populations. Thus, appropriate measures should be taken for effective in situ conservation of wild relatives of crop cultivars. Abstract: Maintaining genetic integrity is essential for in situ and ex situ conservation of crop wild relative (CWR) species. However, introgression of crop alleles into CWR species/populations may change their genetic structure and diversity, resulting in more invasive weeds or, in contrast, the extinction of endangered populations. To determine crop-wild introgression and its consequences, we examined the genetic structure and diversity of six wild rice ( Oryza rufipogon ) populations under in situ conservation in China. Thirty-four simple sequence repeat (SSR) and 34 insertion/deletion markers were used to genotype the wild rice populations and two sets of rice cultivars ( O. sativa ), corresponding to the two types of molecular markers. Shared alleles and STRUCTURE analyses suggested a variable level of crop-wild introgression and admixture. Principal coordinates and cluster analyses indicated differentiation of wild rice populations, which was associated with the spatial distances to cultivated rice fields. The level of overall genetic diversity was comparable between wild rice populations and rice cultivars, but a great number of wild-specific alleles was detected in the wild populations. We conclude based on the results that crop-wild introgression can considerably alter the pattern of genetic structure and relationships of CWR populations. Appropriate measures should be taken for effective in situ conservation of CWR species under the scenario of crop-wild introgression.